The Limits of the Object: On the Notion of Spectrality in Jacques Derrida. (Phenomenology, Humanities and Sciences, 2023)
erence entitled Specters of Marx. As will be seen, the spectral is an elusive category that escapes the temptation of being placed on one side or the other of the usual dichotomy raised between presence and absence, the real and the virtual and, of course, life and death. In this way, Derrida will challenge traditional ontology by demonstrating the constitutive porosity of the border drawn between being and non-being which, he assures, manifests the dislocated nature of reality. The notion of spectrality enables a new way of thinking politic as an activity oriented towards a horizon of justice, motivated by that surplus of the present represented by the generations already dead and those not yet born, whose pressure on the living will make it impossible to consider a closure of the conflict or an end of the history.
Keywords: Spectrum; Onthology; Politic